MODEL COMMUNITY DEVELOPMENT SEBAGAI STRATEGI PEMBERDAYAAN BERBASIS KEARIFAN LOKAL - Suswanto, Bambang; Handoko, Waluyo; Sabiq, Ahmad (Jurnal Review Politik, 2013)
Pasuruhan Village Binangun district of Cilacap as the location of this research was the village that was attented by the public both nationally and internationally after the arrest of suspected terrorists in 2009. This study used a Participatory Rural Appraisal (PRA) through Focus Group Discussion (FGD), interviews, observation and documenttation. The results of study through three business groups (Sharia cooperative of Abdimas Sejahtera, a group of cattle farming and catfish, as well as small business group) resulted a model of community development in the empowerment program which formed by training and mentoring to enhance the resources and managerial capabilities, and training programs for all business groups to become members of the cooperative. This will be strengthen the institutional and cooperative capital